3-D point defect density distributions in thin film Cu(In, Ga)Se2 measured by atom probe tomography. (1st January 2016) - Stokes, Adam; Al-Jassim, Mowafak; Diercks, David R.; Egaas, Brian; Gorman, Brian
Abstract: This paper will discuss the findings of an ordered vacancy compound (OVC) phase that exists deep into the bulk of a high-efficiency Cu(In, Ga)Se2 (CIGS) absorber that is shown to be a result of many ordered defect pairs of 2VCu  + (In, Ga)Cu as determined by atom probe tomography (APT). To date, literature has shown that absorbers grown with the three-step process exhibit the OVC Cu(In, Ga)3 Se5 (135 phase) only within the first few nanometers from the CdS/CIGSe interface and at grain boundaries. In this contribution, we have found a small volume (100 nm × 100 nm × 300 nm) of an OVC phase to exist about 400 nm into the absorber. We show through concentration and density profiles that the concentration change from the stoichiometric Cu(In, Ga)Se2 to the OVC is indeed a result of many ordered defect pairs. We use this volume to perform point defect density distributions to give unique insight to the band structure at the nanoscale. Graphical abstract: